The Broken Pot: An Existentialist Study of The Narrow Path - Adeniran, Morenike A.; Adegbite , Olajumoke O. (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Culture represents experiences, values, behaviour, skills and traditions among others; that we have received from the previous generation, that is, from our forefathers. Culture is what they have learned in life and found as good, workable and beautiful; hence they have passed it on to the next generation so as to maintain a good life. However, our comptemporary Yoruba society has changed so drastically from what it used to be, the old social institutions that ensured the continuty of certain cultural practices have become irrelevant. Using a structuralist approach to studying The Narrow Path, this essay explores the narrative of a maiden who loses her virginity before marriage and the consequences of her action. Structuralism tries to bring together a variety of approaches under a unified program in the study of any cultural activity. These approaches include an examination of the social background from which a product (e.g. a tale) comes, just as we have seen the anthropologists do; an anatomy of the tale to work out the abstract structure of relationships between the various units of its composition (especially the symbols) and most importantly an effort to demonstrate the psychological problem within the culture which the tale is trying to resolve by way of a confrontation between these constituent symbols. However, Existentialism states that because of the world's absurdity, at any point in time, anything can happen to anyone, and a tragic event could plummet someone into direct confrontation with the Absurd. Thus, this paper argues that the influence of modernity on the Yoruba culture gave birth to the loss of certain cultural values as seen in the film.